Understanding physical activity in adolecents with cerebral palsy from a self-determination theoretical perspective : a mixed method case study - Ruiz Egea, Alfredo (2018)
Ruiz Egea, Alfredo, 2018. Understanding physical activity in adolescents with cerebral palsy from a self-determination theoretical perspective: a mixed method case study. Master´s Thesis in Sport and Exercise Psychology. Faculty of Sport and Health Sciences. University of Jyväskylä. 75 p. The amount of research in cerebral palsy has augmented considerably during last twenty years. Increasing functional capacity in population with cerebral palsy, through physical activity has been the main goal of the research in this field during the past decades. Research sustains its effort in a basic assumption, that an increase in functionality will be followed by an increase in physical activity behavior, consequently health benefits are expected. Unfortunately, positive results are limited to the environment of the intervention and therefore not sustained in time. Recent research has started to explore alternatives to foster sustained physical activity behavior after intervention. It has become one of the main current challenges in the field of cerebral palsy, a challenge that it is still unanswered. Based on self-determination theory (Deci & Ryan, 2000), the aim of the present research was to describe and understand the elements involved in initiating and maintaining a physical activity behavior among three Finnish adolescents with cerebral palsy. This is an abductive (both theory and data driven) mixed method case study. Data was collected during a three-month intervention study (EXECP study) which aimed at increasing functional capacity and physical activity levels among the participants. Participants filled quantitative questionnaires assessing: motivational regulation; perceived competence, autonomy support and social support; physical activity; intentions and perceived limitations to be physically active. In addition, indirect and direct qualitative observation and interviews, were used. Quantitative data was analysed via descriptive analysis using IBM SPSS statistics software, while qualitative data was analysed through narrative and descriptive analyses. According to the results, intrinsic forms of motivation towards physical activity and support of the satisfaction of the psychological basic needs, and high PA were found among two participants. External forms of motivation towards physical activity and lack of support of the satisfaction of the psychological basic needs, and low PA were found in one of the participants. Additionally, the results suggest that perceived internal and external barriers towards physical activity, and intentions towards PA, can be related with the level of physical behavior among participants. These results are in line with the tenets of the Self-Determination Theory. Additionally, the results help in understanding physical activity among persons´ with CP and help in planning and implementing fitness and physical activity interventions targeting adolescents with cerebral palsy. Further research is needed in the field to study if the results are transferable to other participants.